Academic Motherhood: Mid‐Career Perspectives and the Ideal Worker Norm. Issue 176 (December 2016) - Ward, Kelly; Wolf‐Wendel, Lisa
Abstract : This chapter explores how mid‐career tenured women faculty, who are mothers and academics, manage multiple roles. The women represent faculty at a variety of institutional types and in a variety of disciplines. The chapter looks at these experiences in light of ideal worker norms.